Sundanese Ethnomatemics Learning in Improving Mathematical Literacy Ability of Elementary School Students - Mufidah, Mufidah; Karso, Karso (International Conference on Elementary Education, 2020)
Mathematical literacy is an important part of mathematical abilities that must be developed. At the end of 2016, Indonesia appreciated the achievement of the Program for International Student Assessment (PISA) value which increased significantly by 22.1 points. In the test, mathematical literacy experienced a good increase of 11 points. But, it is still considered low compared to other countries. The purpose of this review literature is to analyze Sundanese Ethnomatematics Learning in improving mathematical literacy skills. This article discusses in detail 1) sundanese ethnomatemics learning 2) mathematical literacy skills